Importance of Stakeholder Management for Sustainable Construction Industry - Andreea MAIER; Ioan ASCHILEAN (Communications of International Proceedings, 2020)
Increasing client expectations, high demands related to construction time and cost, and the growing complexity of construction methods have made the building industry dynamic and multifaceted. The internal and external participants on the construction project are recognized as stakeholders, they are actively involved in the project, and the execution of the project can affect positively or negatively their interests. The aim of this paper is to analyze the process used to identify construction stakeholders, the factors used to manage their needs, their expectations and the implications of mismanaging them in the development of sustainable construction projects. To improve the process of stakeholder management in the constructions projects we proposed a set of eleven steps. By adopting the principles of stakeholder management organizations will satisfy better their constituent needs and balance their interests, which in the end will increase the sustainability of the construction industry overall.
Keywords: Stakeholder; stakeholder management; construction sector; construction industry; construction projects; management in construction.